2016
DOI: 10.1177/0741088316668517
|View full text |Cite
|
Sign up to set email alerts
|

Toward Audience Involvement

Abstract: This article explores rhetorical implications of extending the audience of written physician notes in hospital settings to include patients and/or family members (the OpenNotes program). Interviews of participating hospital patients and family members (n = 16) underscored the need for more complex understandings of audience beyond “universal” and “particular” explanations. Interviews were organized around the aspects of comprehension, affect/emotion, and likes/dislikes about receiving notes. Results from these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Examination of the content of other news sources—local, national, and global, as well as new sources, specifically, that appeal to different demographics than the NYT , particularly news sources that draw more conservative, rural, and racially and ethnically diverse readerships—can address whether the frames documented here are consistent across sources or whether new frames occur in different sources, targeting different audiences. Additionally, this study does not account for how people are responding to, using, adapting, building on, or subverting these frames and discourses (refer to Breuch et al, 2016, for important work on involving audiences in writing studies research). To this point, vaccine scholars have shown that qualitative, in-depth interviews are a useful method for rhetoricians and writing studies scholars to track and analyze how individuals link up available discourses, broader health beliefs, and personal vaccine choices and behaviors (Lawrence et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the content of other news sources—local, national, and global, as well as new sources, specifically, that appeal to different demographics than the NYT , particularly news sources that draw more conservative, rural, and racially and ethnically diverse readerships—can address whether the frames documented here are consistent across sources or whether new frames occur in different sources, targeting different audiences. Additionally, this study does not account for how people are responding to, using, adapting, building on, or subverting these frames and discourses (refer to Breuch et al, 2016, for important work on involving audiences in writing studies research). To this point, vaccine scholars have shown that qualitative, in-depth interviews are a useful method for rhetoricians and writing studies scholars to track and analyze how individuals link up available discourses, broader health beliefs, and personal vaccine choices and behaviors (Lawrence et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These reports used a wide range of data. For example, Breuch et al (2016) coded interview data from hospital patients and their families for recurring themes. Martinez et al (2015) coded video data for the cognitive activities students used while writing syntheses.…”
Section: The Important Role Coding Plays In Many Fieldsmentioning
confidence: 99%